2007
DOI: 10.1128/iai.00139-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Campylobacter jejuni Protein That Cross-Reacts with Cholera Toxin

Abstract: The question of whether Campylobacter jejuni produces a cholera toxin-like toxin (CTLT) has been controversial. The objective of this study was to identify the factor that cross-reacts with CT from C. jejuni. Filtrates of C. jejuni grown in four different liquid media reported to promote CTLT production were tested by Chinese hamster ovary (CHO) cell elongation assay and for reactivity with CT antibody using GM1 ganglioside enzyme-linked immunosorbent assay (ELISA) and immunoblotting. Protein sequence was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Due to the fact that PorA (MOMP, Cj1259) is the major OMP of C. jejuni (Albert et al , 2007; Clark et al , 2007), it was an obvious choice as an outer-membrane marker (antibodies against MOMP were a kind gift from Qijing Zhang, Iowa State University). This protein has been well documented in the literature as an OMP.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact that PorA (MOMP, Cj1259) is the major OMP of C. jejuni (Albert et al , 2007; Clark et al , 2007), it was an obvious choice as an outer-membrane marker (antibodies against MOMP were a kind gift from Qijing Zhang, Iowa State University). This protein has been well documented in the literature as an OMP.…”
Section: Resultsmentioning
confidence: 99%
“…There is uncertainty on the production of CTLT by C. jejuni . Our recent work indicated that the major outer membrane protein (MOMP-PorA) of C. jejuni cross-reacts with cholera toxin (CT) which would likely have misled investigators that C. jejuni produces a CTLT [5]. It is believed that the cytotoxin(s) may mediate inflammatory diarrhoea that is characteristic of infection in individuals in developed countries [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ileal loop fluids did not cause CHO cell elongation. In the GM1 ELISA, CAYE filtrates from two Swedish strains, the Australian strain and 16 Kuwaiti strains were positive7.…”
Section: Resultsmentioning
confidence: 99%
“…However, a rabbit polyclonal antibody raised against the GST-PorA failed to react with-CT in the immunoblot. This suggested that the reaction was a one-way reaction7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation